1974
DOI: 10.1002/eji.1830040905
|View full text |Cite
|
Sign up to set email alerts
|

Induction of B cell tolerance to polysaccharides by exhaustive immunization and during immunosuppression with cyclophosphamide

Abstract: Mice immunized with an optimal (10 pg), but not suboptimal, dose of levan (LE) became specifically unresponsive to a second dose given 2-8 weeks later. No evidence which could implicate an active suppression mechanism was found. In particular (a) spleen cells from unresponsive donors did not inhibit normal cells in a transfer system; (b) equilibration of serum antibody following 2 days celomic parabiosis between LE-treated and normal mice did not impair responsiveness of the latter, It was concluded that B cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

1975
1975
2014
2014

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(11 citation statements)
references
References 22 publications
0
11
0
Order By: Relevance
“…(b) That DNP-FIC and DNP-OEt starch,elicited very prolonged IgM anti-DNP responses over a wide dose range (Table 1). Dextran B512-2000 [9] and dextran B1355 [lo] also elicit prolonged IgM antibody responses at comparable doses, although at high doses (10 mg) or at much lower doses given during cyclophosphamide suppression they are tolerogenic.…”
Section: Discussionmentioning
confidence: 99%
“…(b) That DNP-FIC and DNP-OEt starch,elicited very prolonged IgM anti-DNP responses over a wide dose range (Table 1). Dextran B512-2000 [9] and dextran B1355 [lo] also elicit prolonged IgM antibody responses at comparable doses, although at high doses (10 mg) or at much lower doses given during cyclophosphamide suppression they are tolerogenic.…”
Section: Discussionmentioning
confidence: 99%
“…We report here o n the effect of epitope density variations t W on the primary in vivo immunogenicity and "high zone" tolerogenicity of DNP conjugates with SIII, levan and dex-n ul trans (B512 and B1299), together with their capacities to induce tolerance via immunization ("exhaustion") and du-: 1 0 2 k 2 n ring suppression with cyclophosphamide (CP) [8].…”
Section: 'mentioning
confidence: 99%
“…Studies have shown that treatment with high doses of dextran itself can tolerize mice (16), and it was possible that the chemical manipulation that was used to prepare the toxogen had produced a modified dextran that was an unusually good tolerogen. To eliminate this possibility, cytidine, a noncytotoxic analog of araC, was coupled to oxidized dextran by the same procedures as those used to prepare the toxogen.…”
Section: Resultsmentioning
confidence: 99%